Temperature effects on molecular processes which lead to stage differentiation in Leishmania (1988)
ABSTRACT: We have studied the effects of growth phase and temperature on the morphological and molecular processes that occur during stage differentiation of Leishmania. Parasites which differ in their ability to transform axenically were compared. A typical heat shock response is observed in strains that transform axenically. Heat shock proteins (HSPs) of 70 and 83 kd are transcribed and synthesized along with a decrease in cellular protein synthesis, including tubulin. Changes in the transcription of the tubulin gene are also noted. In strains which do not transform in culture HSPs are induced, but cellular protein synthesis is unaffected and no differences are observed in tubulin transcription and expression. HSPs 70 and 83 remain constitutively expressed in amastigotes. HSP 83 transcription increases along the promastigote growth curve. beta-Tubulin transcription is also affected by growth phase and temperature increase, though alpha-tubulin remains unaltered. An amastigote-like hybridization pattern is induced in heat-shocked promastigotes, in which a larger transcript for beta-tubulin (2.8 kb) becomes dominant and the promastigote transcript (2.4 kb) decreases. Tubulin expression is susceptible to temperature control in Leishmania mexicana amazonensis, though direct correlation to HSP expression was not demonstrated.